Youth’s acceptance toward streamyx broadband packages by TM Point Kuala Krai, Kelantan / Amir Hamzah Rahim - Rahim, Amir Hamzah (2013)
The researcher study youth’s acceptance toward streamyx broadband packages by TM point Kuala Krai, Kelantan. There are five (5) factors in the study which is perceived financial cost, compatibility, perceived usefulness, perceived ease of use and trust in order to see the affecting factors that influence the acceptance of youth’s customers. The objective of this study is to see the important and least factors that influence youth’s acceptance toward streamyx broadband packages by TM Point in Kuala Krai. Then, this study can give suggestions and recommendations to TM Point on how to attract more customers based on the findings of youth’s acceptance. Data were gathered from the questionnaires which were distributed to 100 respondents that visit TM point and public nearest. The data were analyzed using SPSS through the reliability analysis, frequencies analysis, cross tabulation, correlation coefficient analysis, mean analysis and regression. From the result, the researcher found that perceived financial cost, compatibility, perceived usefulness, perceived ease of use and trust have a positive significant relationship with the youth’s acceptance. From the findings, it shows that perceived usefulness is the most important factors (mean=4.2657) while compatibility is the least important factors (3.9129). Some conclusions are provided in this research and the researcher also stated several recommendations based on the results. It is a great pleasure if TM Point is willing to evaluate the suggestions from the respondents and the researcher and propose to the Telekom Malaysia Berhad.